Neighborhood by neighborhood: community policing in a rust belt city. Issue 2 (9th July 2018) - Cooley, Will; Bemiller, Michelle; Jefferis, Eric; Penix, Rose
Abstract : Purpose: The purpose of this paper is to examine citizen satisfaction with police services and perceived safety using survey research in two high crime neighborhoods. Problem-oriented crime deterrence strategies were used in one neighborhood, the other served as a control group. Design/methodology/approach: Mixed-methods approach was used to measure the effectiveness of problem-oriented approaches in persistent high-crime areas. Pre- and post-intervention surveys were conducted by sampling addresses in both neighborhoods and analyzing results. Findings: No between-neighborhood differences were reported regarding the satisfaction with police services or improvement in perceived safety. Originality/value: These findings suggest that this deterrence strategy is a promising approach to reducing crime while not damaging community perceptions. However, departments must vary place-based strategies, and prevention is difficult given historical contexts, the absence of credible community partners and limited resources in a declining city.